FORMULASI SEDIAAN SIRUP PENINGKAT IMUNITAS DARI HERBA MENIRAN (Phyllanthus niruri L.) - W. O. Sugarda; K.D.C. Dewi; K.W.A. Putra; M.B. Yogiswara; C.B.A.C. Sukawati; P.A.R. Sutresna; N.L.G.J. Dewi; C.I.S. Arisanti; P.S. Yustiantara (Jurnal Kimia (Journal of Chemistry), 2019)
Meniran herb (Phyllanthus niruri L.) is a plant that has been scientifically proven to have activity as a natural immunomodulator. The effectiveness of natural immunomodulators from meniran herbs can be improved by formulating the ethanolic extract of meniran herbs into syrup preparations. This research was conducted to find out that the herbal extracts obtained had fulfilled the parameters of extract quality standards so that they could be formulated into pharmaceutical products. Standardization of herbal extracts includes testing of moisture content, testing of total ash content, testing of acid-soluble ash content, and testing of total flavonoid levels. Ethanol extract of Meniran herbs was obtained by maceration using 95% ethanol. Testing the extract moisture content produced extracts with a moisture content of 7.295%. Total ash content was 3%, acid insoluble ash content was 1.2% and total flavonoid content was 3.15%. Keywords: formulation, immunity, syrup, Phyllanthus niruri L.